On-chip optical detection of viruses : a review - Shi, Yuzhi (2021)
The current outbreak of the coronavirus disease-19 (COVID-19) pandemic worldwide has caused millions of fatalities and imposed a severe impact on our daily lives. Thus, the global healthcare system urgently calls for rapid, affordable, and reliable detection toolkits. Although the gold-standard nucleic acid amplification tests have been widely accepted and utilized, they are time-consuming and labor-intensive, which exceedingly hinder the mass detection in low-income populations, especially in developing countries. Recently, due to the blooming development of photonics, various optical chips have been developed to detect single viruses with the advantages of fast, label-free, affordable, and point of care deployment. Herein, optical approaches especially in three perspectives, e.g., flow-free optical methods, optofluidics, and surface-modification-assisted approaches, are summarized. The future development of on-chip optical-detection methods in the wave of emerging new ideas in nanophotonics is also briefly discussed.